Tetrazole Ring Substitution at Carbon and Boron Sites of the Cobalt Bis(dicarbollide) Ion Available via Dipolar Cycloadditions - El Anwar, Suzan; Růžičková, Zdeňka; Bavol, Dmytro; Fojt, Lukáš; Grüner, Bohumír (Inorganic chemistry, 2020)
Herein, we describe the synthesis of two families of compounds accessible from [3 + 2] cycloaddition reactions of known B8-substituted isonitrilium and new C1-alkylnitrile and C(1,1')-dialkylnitrile derivatives of the [(1,2-C2B9H11)2-3,3'-Co(III)]- ion with an azide ion that produce a tetrazole ring substitution at the cobaltacarborane cage. In addition, we outline the important differences in reactivity observed for the two types [B-isonitrilium/C-(alkyl)nitrile] of cobaltacarborane derivatives. The first family of compounds described corresponds to C5-atom-boronated tetrazole rings, with the five-membered moiety in the second type being doubly substituted at the N1 and C5 positions. This substitution opens cobaltacarborane chemistry to a new type of functional group at the cage of potential utility as structural blocks for use in medicinal chemistry or materials science. Our study includes single-crystal X-ray structures of the starting nitriles and both families of tetrazole derivatives, and the structural features that arise from the substitutions are discussed.